2021
DOI: 10.3390/rs14010068
|View full text |Cite
|
Sign up to set email alerts
|

Displacement Characterization and Spatial-Temporal Evolution of the 2020 Aniangzhai Landslide in Danba County Using Time-Series InSAR and Multi-Temporal Optical Dataset

Abstract: On 17 June 2020, a large ancient landslide over the Aniangzhai (ANZ) slope, Danba County, Sichuan Province, China, was reactivated by a series of multiple phenomena, including debris flow triggered by heavy rainfall and flooding. In this study, Synthetic Aperture Radar (SAR) images acquired by the Sentinel-1A/B satellite and optical images captured by the PlanetScope satellites were jointly used to analyze and explore the deformation characteristics and the Spatial-Temporal evolution of the ANZ landslide befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…This, in turn, triggered the movement of the main body of the landslide. Coupled with other secondary hazards induced by the mudslide in Meilong Gully, it impacted 12 townships in the downstream area of the Xiaojinchuan River, affecting the life and property safety of more than 20,000 people [46], [47]. Shortly after the disaster, the emergency response agencies conducted on-site investigations, providing a substantial amount of valuable information for our subsequent study [48], [49].…”
Section: A Study Areamentioning
confidence: 99%
“…This, in turn, triggered the movement of the main body of the landslide. Coupled with other secondary hazards induced by the mudslide in Meilong Gully, it impacted 12 townships in the downstream area of the Xiaojinchuan River, affecting the life and property safety of more than 20,000 people [46], [47]. Shortly after the disaster, the emergency response agencies conducted on-site investigations, providing a substantial amount of valuable information for our subsequent study [48], [49].…”
Section: A Study Areamentioning
confidence: 99%
“…Kuang et al [8] jointly used the Sentinel-1A/B satellite SAR data and the PlanetScope satellites optical images to investigate the deformation time series for the Aniangzhai (ANZ) landslide in Sichuan Province, China. Kuang et al [8] used optical pixel offset tracking (POT) and InSAR techniques to map the pre-and post-failure surface deformation over the ANZ slope.…”
Section: Monitoring Landslide and Slope Stabilitymentioning
confidence: 99%
“…Kuang et al [8] jointly used the Sentinel-1A/B satellite SAR data and the PlanetScope satellites optical images to investigate the deformation time series for the Aniangzhai (ANZ) landslide in Sichuan Province, China. Kuang et al [8] used optical pixel offset tracking (POT) and InSAR techniques to map the pre-and post-failure surface deformation over the ANZ slope. Kuang et al [8] was able to identify and characterize several areas of pre-failure movements before the re-activation of the ANZ landslide, and suggested that the most significant triggering factor for the landslide was because of the heavy rainfall.…”
Section: Monitoring Landslide and Slope Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Interferometric Synthetic Aperture Radar (InSAR), an ideal and effective remote sensing method for monitoring ground deformation, has been widely utilized for this purpose. InSAR has already been successfully applied for monitoring a range of ground displacement applications over the past 20 years, including glacier motion [14], earthquake deformation [15,16], volcanic movement [17], fluid flow [18,19], slope stability monitoring [20], mining activities [21], etc. Compared to conventional geodetic monitoring techniques, InSAR offers a low-cost and low-labor way to measure surface displacement over large spatial coverages with a high accuracy of centimeters or even millimeters [22][23][24].…”
Section: Introductionmentioning
confidence: 99%